Analysis of Metaphors and Their Meanings in Ashe's Selected Songs: A Semantic Study - Rumahorbo, Elisa Apprilia Vinayaka; Rajagukguk, Rosdiana; Sihite, Jubil Ezer (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. Semantics is a branch of linguistics that aims to reveal a certain meaning. This research aims to analyze the use of metaphors and their meanings in Ashe's selected songs lyrics through a semantic approach. Metaphor is one of the elements that is often used in song lyrics to convey messages implicitly and deeply. In this research, descriptive qualitative method is used to identify the types of metaphors based on Lakoff and Johnson's conceptual theory, and interpret the meaning of the metaphors using semantic approach. The research data were taken from the lyrics of 13 selected songs by Ashe. The results show that in the lyrics of Ashe's selected songs, metaphors are used to describe feelings and experiences. Metaphors such as “love as a physical feeling” were found to have meanings that describe emotional feelings. The use of metaphors in Ashe's song not only beautifies the lyrics, but also creates a broader interpretation of meaning for the listener. Keywords: Semantics, Structural Metaphor, Orientational Metaphor, Ontological Metaphor, Songs.